Analisis Penyebab Keterlambatan Pembangunan Proyek Konstruksi pada Pembangunan Rusun Dosen Politeknik Pekerjaan Umum (Indonesian Journal of Civil Engineering Study, 2025)
Construction delays occur when the project implementation time exceeds the agreed limit, which can be seen from the non-conformity of the project schedule. Various factors that cause delays include materials, labor, equipment, finances, natural conditions, relationships with project owners, and changes that occur during the project. These delays affect the initial agreed plans and have the potential to cause financial problems, leading to extended project completion times and increased costs required. This research was carried out on the Public Works Polytechnic Lecturer Flat Construction project through a questionnaire filled out by 30 respondents, with data analyzed using Likert and Ms. Excel scales. The results of the analysis showed that the project experienced delays, with the main causes being changes in demand from project owners (mean 3.27), schedule discrepancies (mean 3.23), and delays in material delivery (mean 3.23). The largest impact identified was the increase in costs that exceeded the initial estimate (mean 3.20). The recommended solution is to conduct a joint evaluation between office staff and field workers to improve work schedules (mean 3.43)
Keywords: Construction; Delays; Labor; Materials; Projects